Developing a framework for tracking antimicrobial resistance gene movement in a persistent environmental reservoir - Mathers, AJ; Li, TJX; He, Q; Narendra, S; Stoesser, N; Eyre, DW; Walker, AS; Barry, KE; Castañeda-Barba, S; Huang, FW; Parikh, H; Kotay, S; et al. (Springer Nature, 2024)
Mobile genetic elements are key to the global emergence of antibiotic resistance. We successfully reconstructed the complete bacterial genome and plasmid assemblies of isolates sharing the same blaKPC carbapenemase gene to understand evolution over time in six confined hospital drains over five years. From 82 isolates we identified 14 unique strains from 10 species with 113 blaKPC-carrying plasmids across 16 distinct replicon types. To assess dynamic gene movement, we introduced the ‘Composite-Sample Complex’, a novel mathematical approach to using probability to capture the directional movement of antimicrobial resistance genes. The Composite Sample Complex accounts for the co-occurrence of both plasmids and chromosomes within an isolate, and highlights likely gene donors and recipients. From the validated model, we demonstrate frequent transposition events of blaKPC from plasmids to other plasmids, as well as integration into the bacterial chromosome within specific drains. We present a novel approach to estimate the directional movement of antimicrobial resistance via gene mobilization.